Nebivolol Desensitizes Myofilaments of a Hypertrophic Cardiomyopathy Mouse Model - Stücker, Sabrina; Kresin, Nico; Carrier, Lucie; Friedrich, Felix W. (Frontiers in Physiology, 2017)
Background. Hypertrophic cardiomyopathy (HCM) patients often present with diastolic dysfunction and a normal to supranormal systolic function. To counteract this hypercontractility, guideline therapies advocate treatment with beta-adrenoceptor and Ca2+ channel blockers. One well established pathomechanism for the hypercontractile phenotype frequently observed in HCM patients and several HCM mouse models is an increased myofilament Ca2+ sensitivity. Nebivolol, a commonly used beta-adrenoceptor antagonist, has been reported to lower maximal force development and myofilament Ca2+ sensitivity in rabbit and human heart tissues. The aim of this study was to evaluate the effect of nebivolol in cardiac muscle strips of an established HCM Mybpc3 mouse model. Furthermore, we investigated actions of nebivolol and epigallocatechin-gallate, which has been shown to desensitize myofilaments for Ca2+ in mouse and human HCM models, in cardiac strips of HCM patients with a mutation in the most frequently mutated HCM gene MYBPC3. Methods and Results. Nebivolol effects were tested on contractile parameters and force-Ca2+ relationship of skinned ventricular muscle strips isolated from Mybpc3-targeted knock-in (KI), wild-type (WT) mice and cardiac strips of three HCM patients with MYBPC3 mutations. At baseline, KI strips showed no difference in maximal force development compared to WT mouse heart strips. Neither 1 nor 10 µM nebivolol had an effect on maximal force development in both genotypes. 10 µM nebivolol induced myofilament Ca2+ desensitization in WT strips and to a greater extent in KI strips. Neither 1 nor 10 µM nebivolol had an effect on Ca2+ sensitivity in cardiac muscle strips of three HCM patients with MYBPC3 mutations, whereas epigallocatechin-gallate induced a right shift in the force-Ca2+ curve. Conclusion. Nebivolol induced a myofilament Ca2+ desensitization in both WT and KI strips, which was more pronounced in KI muscle strips. In human cardiac muscle strips of three HCM patients nebivolol had no effect on myofilament Ca2+ sensitivity.